2022
DOI: 10.3390/ijms231911459
|View full text |Cite
|
Sign up to set email alerts
|

Macropore Regulation of Hydroxyapatite Osteoinduction via Microfluidic Pathway

Abstract: Macroporous characteristics have been shown to play a key role in the osteoinductivity of hydroxyapatite ceramics, but the physics underlying the new bone formation and distribution in such scaffolds still remain elusive. The work here has emphasized the osteoinductive capacity of porous hydroxyapatite scaffolds containing different macroporous sizes (200–400 μm, 1200–1500 μm) and geometries (star shape, spherical shape). The assumption is that both the size and shape of a macropore structure may affect the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Microporous hydroxyapatite (HA) scaffolds with 0.4 μm pore sizes exhibit osteogenic potential, as hydroxyapatite nanocrystals display superior adsorption of albumin and fibronectin. Further, it is also observed that structural design influences bioactivity; concave scaffolds induce bone formation within pores and its concave surfaces, while osteoblasts preferentially attach to grooved scaffold surfaces . Microporosities not only enhance the surface area for protein adsorption but also induce capillarity, anchoring, and accommodating cells within micropores, even if their dimension is slightly smaller than the cell …”
Section: Role Of Trabecular Microarchitecture In Scaffold Bioactivitymentioning
confidence: 99%
“…Microporous hydroxyapatite (HA) scaffolds with 0.4 μm pore sizes exhibit osteogenic potential, as hydroxyapatite nanocrystals display superior adsorption of albumin and fibronectin. Further, it is also observed that structural design influences bioactivity; concave scaffolds induce bone formation within pores and its concave surfaces, while osteoblasts preferentially attach to grooved scaffold surfaces . Microporosities not only enhance the surface area for protein adsorption but also induce capillarity, anchoring, and accommodating cells within micropores, even if their dimension is slightly smaller than the cell …”
Section: Role Of Trabecular Microarchitecture In Scaffold Bioactivitymentioning
confidence: 99%
“…In contrast, the pore size should ideally be greater than 200 µm or even greater than 250 µm to facilitate internal bone growth and the colonization and proliferation of osteoblasts within the large pores [87]. Leet et al found that a scaffold with 500 µm macroporous pores produced more osseointegration and bone regeneration than a scaffold with 250 µm macroporous pores in vivo [88][89][90]. Graphene oxide-hydroxyapatite (GO-HAP) is a 2D nanocomposite prepared by in situ bonding.…”
Section: Polylactic Acid (Pla)mentioning
confidence: 99%
“…6 Given the similarities with natural bone chemistry, osteoinductive bioceramic materials have inspired the interest of researchers. 7,8 Moreover, bioceramics have good surface characteristics including roughness, dispersion, and porosity, and they might contribute to osteoblast adhesion and proliferation, hence promoting osteogenesis. 9 Calcium phosphates in the form of hydroxyapatite (HA) are an excellent material option for the preparation of 3D porous scaffolds in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%